Characterization of meiotic recombination intermediates through gene knockouts in founder hybrid mice - Davies, Benjamin; Zhang, Gang; Moralli, Daniela; Alghadban, Samy; Biggs, Daniel; Preece, Chris; Donnelly, Peter; Hinch, Anjali Gupta

(untitled) (Genome Research, 2023)
Mammalian meiotic recombination proceeds via repair of hundreds of programmed DNA double-strand breaks, which requires choreographed binding of RPA, DMC1, and RAD51 to single-stranded DNA substrates. High-resolution in vivo binding maps of these proteins provide insights into the underlying molecular mechanisms. When assayed in F1-hybrid mice, these maps can distinguish the broken chromosome from the chromosome used as template for repair, revealing more mechanistic detail and enabling the structure of the recombination intermediates to be inferred. By applying CRISPR-Cas9 mutagenesis directly on F1-hybrid embryos, we have extended this approach to explore the molecular detail of recombination when a key component is knocked out. As a proof of concept, we have generated hybrid biallelic knockouts of Dmc1 and built maps of meiotic binding of RAD51 and RPA in them. DMC1 is essential for meiotic recombination, and comparison of these maps with those from wild-type mice is informative about the structure and timing of critical recombination intermediates. We observe redistribution of RAD51 binding and complete abrogation of D-loop recombination intermediates at a molecular level in Dmc1 mutants. These data provide insight on the configuration of RPA in D-loop intermediates and suggest that stable strand exchange proceeds via multiple rounds of strand invasion with template switching in mouse. Our methodology provides a high-throughput approach for characterization of gene function in meiotic recombination at low animal cost.